Evaluation of the importance of mixing during preparation of antibiotic infusions - Ina Barzel; Janique Gabriëlle Jessurun; Soma Bahmany; Paul Hugo Marie van der Kuy; Birgit Catharina Peter Koch; Nicole Geertruida Maria Hunfeld (BMC, 2022)
Abstract Background The mixing step after medication addition to the infusion bag is frequently omitted during the preparation of drug infusions. However, the importance of mixing when preparing antibiotic infusions is still unknown. Methods The primary aim of this study was to assess the importance of the mixing step by comparing the concentrations of unmixed antibiotic infusions (cefuroxime, flucloxacillin, meropenem, and vancomycin) with the declared concentration at regular intervals during infusion. The secondary aim was to compare concentrations between preparation sites (hospital pharmacy versus clinical ward). Infusion bags were run through electronic infusion pumps. For cefuroxime, flucloxacillin, and meropenem, samples were collected 1, 15, and 20 min after starting the administration (infusion duration: 30 min). For vancomycin, samples were collected after 1, 60, and 110 min (infusion duration: 120 min). Vancomycin concentrations were measured using the Architect c4000 analyser and other concentrations using a validated UPC2-MS-MS multimethod. Results The median concentrations of the four antibiotics were comparable to the declared concentration at all three time points. No significant differences were found between preparation sites. Conclusions Spontaneous mixing occurred in the examined antibiotic solutions during normal handling.